PENGARUH PEMBIASAAN MENGHAFAL PERKALIAN TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA KELAS IV SD NEGERI MEJING 2 - Damar Kusuma Jati; Elsa Nur Safitri; Fauziyah Nur Aulia; Nadya Khairunnisa; Rahayu Bunga Gupita; Susan Kurnia Sari; Henry Aditia Rigianti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The aim of this research was to gain a better understanding of how learning outcomes are influenced by the habit of memorizing multiplication in mathematics learning. The method used is quantitative experiment. School administrators, teachers and students at SD Negeri Mejing 2 were the focus of this research. The data collection technique for this research used written tests in classes IVA and IVB. This research used the Mann-Whitney statistic test with the average mathematics learning outcomes for class IVA obtained being greater than class IVB. So the habit of memorizing multiplication affects learning outsomes.